ENVIRONMENTAL CRITICAL THINKING : THE ROLE OF PROBLEM BASED LEARNING INTEGRATED WITH INSTAGRAM GREENPEACEID - Nabila Nirwasita Chairunnisa; Dwiyono Hari Utomo; Budi Handoyo; Heni Masruroh (GEOGRAPHY : Jurnal Kajian, Penelitian dan Pengembangan Pendidikan, 2025)
Abstrack: This study was motivated by increasing environmental damage. Critical thinking abilities are developed through education, which helps students get ready for future environmental issues. Geography learning at MAN 1 Malang is still dominated by a teacher-centred learning model, which is ineffective in developing students' critical thinking abilities. The purpose of this study is to investigate how Grade XI students' critical thinking abilities are affected when the Problem-Based Learning (PBL) model integrated with Instagram Greenpeaceid. The method used is a quasi-experimental design with a post-test only control group, involving an experimental class and a control class. The experimental class uses PBL integrated Instagram, while the control class uses the Direct Instruction method. There was a substantial difference between the two classes, based on the independent sample t-test results, which revealed significance at 0.005 < 0.05. These results show that using Instagram Greenpeaceid integrated with the PBL paradigm successfully improves students' critical thinking abilities through logical, argumentative, and collaborative discussion and presentation activities. This integration also supports the achievement of 21st-century competencies in geography education. Abstrak: Penelitian ini dilatar belakangi oleh kerusakan lingkungan yang semakin meningkat. Pendidikan berperan penting dalam mengembangkan keterampilan berpikir kritis guna mempersiapkan siswa menghadapi tantangan lingkungan di masa depan. Pembelajaran geografi di MAN 1 Malang masih didominasi model teacher centered, yang kurang efektif dalam mengembangkan kemampuan berpikir kritis siswa. Penelitian ini bertujuan mengkaji pengaruh model Problem-Based Learning (PBL) terintegrasi Instagram Greenpeaceid terhadap keterampilan berpikir kritis siswa kelas XI. Metode yang digunakan adalah quasi-experiment dengan desain post-test only control group, melibatkan kelas eksperimen dan kontrol. Kelas eksperimen menggunakan PBL terintegrasi Instagram, sedangkan kelas kontrol menggunakan Direct Instruction. Hasil uji independent sample t-test menunjukkan signifikansi 0,005 < 0,05, yang berarti terdapat perbedaan signifikan antara kedua kelas. Temuan ini menunjukkan bahwa penerapan model PBL terintegrasi Instagram Greenpeaceid efektif meningkatkan keterampilan berpikir kritis siswa melalui kegiatan diskusi dan presentasi yang logis, argumentatif, dan kolaboratif. Integrasi ini juga mendukung pencapaian kompetensi abad ke-21 dalam pembelajaran geografi.